Change in urban and non-urban pattern of ED use during the COVID-19 pandemic in 28 Michigan hospitals: an observational study. Issue 2 (5th February 2021) - Keyes, Daniel; Hardin, Blake; Sweeney, Brian; Shedden, Kerby
Abstract : Objective: To assess the trends in visits, overall and by age, to urban and non-urban emergency departments (EDs), and visits resulting in admission to hospital before and during the COVID-19 pandemic using a large regional database. Setting: A large regional database of 28 EDs during the COVID-19 pandemic in Michigan, with an index case of 11 March 2020 and peak in the first week of April. Participants: ED visits during the first 5 months of the calendar year were included and compared with the previous year. Facilities where these participants were seen were classified as urban or non-urban, with comparisons of total visits, COVID-like cases, paediatric and trauma. Outcome measures: Daily visits to EDs of patients presenting with COVID-like symptoms, trauma, age patterns and total cases, and stratified between urban and non-urban settings. Results: There were 1 732 852 visits across the 2 years, 953 407 between study and comparison periods, and 457 130 visits defined as COVID-like (median age 44 years). Total ED visits decreased to 48% of the previous year, showing a delayed-inverse relationship with COVID-19. Trauma cases dropped but returned to the pre-COVID-19 rate by the end of May in Urban centres. Paediatric cases decreased to 20% of the previous year by the end of April. The oldest age groups showed the least change in ED visits in response to the pandemic. Conclusions: This large US Midwestern state study describes a dramatic decrease in ED visits after the onset of the COVID-19 pandemic in Michigan, including stratification by varying ages and trauma, demonstrating the tangible impact of the COVID-19 pandemic on urban and non-urban EDs.